A Universal, Sound, and Complete Forward Reasoning Technique for Machine-Verified Proofs of Linearizability - Jayanti, Prasad; Jayanti, Siddhartha; Yavuz, Ugur Y.; Hernandez, Lizzie (Proceedings of ACM on programming languages, 2024)
We introduce simple, universal, sound, and complete proof methods for producing machine-verifiable proofs of linearizability and strong linearizability. Universality means that our method works for any object type; soundness means that an algorithm can be proved correct by our method only if it is linearizable (resp. strong linearizable); and completeness means that any linearizable (resp. strong linearizable) implementation can be proved so using our method. We demonstrate the simplicity and power of our method by producing proofs of linearizability for the Herlihy-Wing queue and Jayanti's single-scanner snapshot, as well as a proof of strong linearizability of the Jayanti-Tarjan union-find object. All three of these proofs are machine-verified by TLAPS (the TLA+ Proof System).